Reduced exposure to malaria vectors following indoor residual spraying of pirimiphos-methyl in a high-burden district of rural Mozambique with high ownership of long-lasting insecticidal nets: entomological surveillance results from a cluster-randomized trial - Joseph M. Wagman; Kenyssony Varela; Rose Zulliger; Abuchahama Saifodine; Rodaly Muthoni; Stephen Magesa; Carlos Chaccour; Christelle Gogue; Kenzie Tynuv; Aklilu Seyoum; Dereje Dengela; Francisco Saúte; et al. (Malaria Journal, 2021)
Abstract Background The need to develop new products and novel approaches for malaria vector control is recognized as a global health priority. One approach to meeting this need has been the development of new products for indoor residual spraying (IRS) with novel active ingredients for public health. While initial results showing the impact of several of these next-generation IRS products have been encouraging, questions remain about how to best deploy them for maximum impact. To help address these questions, a 2-year cluster-randomized controlled trial to measure the impact of IRS with a microencapsulated formulation of pirimiphos-methyl (PM) in an area with high ownership of long-lasting insecticidal nets (LLINs) was conducted in a high-transmission district of central Mozambique with pyrethroid resistant vectors. Presented here are the results of the vector surveillance component of the trial. Methods The 2 year, two-armed trial was conducted in Mopeia District, Zambezia Province, Mozambique. In ten sentinel villages, five that received IRS with PM in October–November 2016 and again in October–November 2017 and five that received no IRS, indoor light trap collections and paired indoor-outdoor human landing collections catches (HLCs) were conducted monthly from September 2016 through October 2018. A universal coverage campaign in June 2017, just prior to the second spray round, distributed 131,540 standard alpha-cypermethrin LLINs across all study villages and increased overall net usage rates in children under 5 years old to over 90%. Results The primary malaria vector during the trial was Anopheles funestus sensu lato (s.l.), and standard World Health Organization (WHO) tube tests with this population indicated variable but increasing resistance to pyrethroids (including alpha-cypermethrin, from > 85% mortality in 2017 to 7% mortality in 2018) and uniform susceptibility to PM (100% mortality in both years). Over the entire duration of the study, IRS reduced An. funestus s.l. densities by 48% (CI95 33–59%; p < 0.001) in indoor light traps and by 74% (CI95 38–90%; p = 0.010) during indoor and outdoor HLC, though in each study year reductions in vector density were consistently greatest in those months immediately following the IRS campaigns and waned over time. Overall there was no strong preference for An. funestus to feed indoors or outdoors, and these biting behaviours did not differ significantly across study arms: observed indoor-outdoor biting ratios were 1.10 (CI95 1.00–1.21) in no-IRS villages and 0.88 (CI95 0.67–1.15) in IRS villages. The impact of IRS was consistent in reducing HLC exposures both indoors (75% reduction: CI95 47–88%; p = 0. < 0.001) and outdoors (68% reduction: CI95 22–87%; p = 0.012). While substantially fewer Anopheles gambiae s.l. were collected during the study, trends show a similar impact of IRS on this key vector group as well, with a 33% (CI95 7–53%; p = 0.019) reduction in mosquitoes collected in light traps and a non-statistically significant 39% reduction (p = 0.249) in HLC landing rates. Conclusion IRS with PM used in addition to pyrethroid-only LLINs substantially reduced human exposures to malaria vectors during both years of the cluster-randomized controlled trial in Mopeia—a high-burden district where the primary vector, An. funestus s.l., was equally likely to feed indoors or outdoors and demonstrated increasing resistance to pyrethroids. Findings suggest that IRS with PM can provide effective vector control, including in some settings where pyrethroid-only ITNs are widely used. Trial registration clinicaltrials.gov , NCT02910934. Registered 22 September 2016, https://www.clinicaltrials.gov/ct2/show/NCT02910934.